JURIDICAL NORMATIVE REVIEW OF CONVERSION CONVENTIONAL BANKS INTO ISLAMIC BANK AFTER THE PROMULGATION OF QANUN ACEH CONCERNING SHARIA FINANCIAL INSTITUTIONS - Fahrul Fauzi (Berumpun: International Journal of Social, Politics, and Humanities, 2020)
Nowadays, Islamic banks in Indonesia continue to experience growth, one of which is in the Province of Nanggroe Aceh Darussalam. In Aceh, in order to support Islamic financial institutions, Qanun No. 11 of 2018 concerning Islamic Financial Institutions has been formed. It is interesting to review the provisions of Article 65 which reads "When this Qanun comes into force, financial institutions operating in Aceh must adjust to this Qanun no later than 3 (three) years from the enactment of this Qanun". These provisions have an impact on every conventional bank in Aceh that must adjust to Islamic principles. In order to continue to run its business activities in Aceh, conventional banks must make adjustments to implement sharia principles. One form of adjustment is to convert conventional banks into Islamic banks as stipulated in the OJK Regulation Number 64/POJK.03/2016. The approach used by the author in analyzing this problem is a normative juridical approach supported by the literature study method.